Modern Control Systems ELEVENTH EDITION - Dorf, Richard C. (Prentice Hall, 2012)
Written to be equally useful for all engineering disciplines, this book is organized around the concept of control systems theory as it has been developed in the frequency and time domains. It provides coverage of classical control employing root locus design, frequency and response design using Bode and Nyquist plots. It also covers modern control methods based on state variable models including pole placement design techniques with full-state feedback controllers and full-state observers. The book covers several important topics including robust control systems and system sensitivity, state variable models, controllability and observability, computer control systems, internal model control, robust PID controllers, and computer-aided design and analysis. For all types of engineers who are interested in a solid introduction to control systems.